On a hyperbolic equation on a geometric graph with hysteresis type boundary conditions. (1st February 2020) - Kamenskii, Mikhail; Liou, Yeong-Cheng; Wen, Ching-Feng; Zvereva, Margarita
ABSTRACT: In the present paper, we investigate the initial boundary value problem describing oscillation process on a geometric graph with hysteresis type boundary conditions. The analogue of the d'Alembert formula is obtained.